Preparation of ZnO nanowires for solar cells application - Fernandes, S. L. [UNESP]; Varella, J. A. [UNESP]; Matsubara, E. Y. [UNESP]; Longo, E. [UNESP]; Graeff, C. F.D.O. [UNESP]; Zaghete, M. A. [UNESP] (My University, 2014)
In this work we have synthetized ZnO nanowires and composite ZnO-carbon nanotubes (ZnO-CNT) films for application as photoanode in solar cells. The films were synthetized in two steps. In the first one, a seed layer was deposited on FTO coated glass wafer using a Pechini solution. In the second step ZnO nanowires and ZnO-CNT (0.1%wt) was grown by microwave assisted hydrothermal on these tin layer. The results show incorporation of CNT in ZnO nanowires films and it is a promisor material for solar cells.
Keywords: Carbon nanotubes; Solar cells; Zinc oxide